Properti Eigen Untuk Graf k-Regular Tak Terhubung - R. Respitawulan (Matematika, 2017)
Abstract. (eigen properties of non-connected k-regular graph) One of the important properties of an adjacency matrix as a representation of a graph is its eigen property. According to Biggs, a k-regular connected graph will have k as one of its Eigen value and the multiplicity is 1. Here, we investigate the Eigen value and its multiplicity of a non-connected k-regular graph. The result shows if a non-connected k-regular graph has c components, then will be one of its eigen value with the geometric multiplicity of c.Keywords: adjacency matrix, eigen values, geometric multiplicityAbstrak. Salah satu sifat penting dari matriks adjasen sebagai representasi dari graf adalah sifat eigennya. Biggs menyatakan bahwa graf regular terhubung dengan derajat k akan memiliki nilai eigen k yang multiplisitasnya satu. Di sini diselidiki nilai eigen untuk graf k-regular yang tak terhubung. Jika graf k-regular tak terhubung memiliki c buah komponen, maka k akan menjadi salah satu nilai eigen graf tersebut dengan multiplisitas geometri c.Kata kunci: matriks adjasen, nilai eigen, multiplisitas geometri